2019
DOI: 10.1161/jaha.118.011253
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Involvement in Patients With Histologically Diagnosed Cardiac Sarcoidosis: A Systematic Review and Meta‐Analysis of Gross Pathological Images From Autopsy or Cardiac Transplantation Cases

Abstract: Background In patients with suspected cardiac sarcoidosis, late gadolinium enhancement on cardiovascular magnetic resonance imaging and/or 18 F‐fluorodeoxyglucose uptake on positron emission tomography are often used to reach a clinical diagnosis of cardiac sarcoidosis. On the basis of data from the imaging literature of clinical cardiac sarcoidosis, no specific features of myocardial involvement are regarded as pathognomonic for cardiac sarcoidosis. Thus, a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…A meta-analysis of histologically diagnosed CS concluded that there were certain patterns of myocardial involvement in >90% of cases. These findings can improve the diagnosis and prognostication of patients with suspected CS, using CMR and FDG-PET [1].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A meta-analysis of histologically diagnosed CS concluded that there were certain patterns of myocardial involvement in >90% of cases. These findings can improve the diagnosis and prognostication of patients with suspected CS, using CMR and FDG-PET [1].…”
Section: Discussionmentioning
confidence: 78%
“…Sarcoidosis is characterized by a non-caseating granuloma, which is formed via an inflammatory reaction resulting in an accumulation of epithelial cells, monocytes, lymphocytes, macrophages and fibroblasts [1]. There are various histological subtypes [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patchy uptake on a dedicated cardiac PET scan has also been incorporated into the HRS and the WASOG criteria. A crucial element in establishing a diagnosis of cardiac sarcoidosis, even with histology proven extra-cardiac disease, is excluding other causes of LGE, such as coronary artery disease or other non-ischemic cardiomyopathies such as genetic arrhythmogenic cardiomyopathies which could also demonstrate increased myocardial uptake on FDG-PET imaging [42]. Challenges also remain regarding the ideal dietary preparation to suppress normal glucose uptake by the myocardium and avoid false positive FDG-PET.…”
Section: Discussionmentioning
confidence: 99%
“…При этом излюбленной локализацией является стенка левого желудочка (ЛЖ) (преимущественно ее средняя часть и субэпикардиальная область) и межжелудочковая перегородка (МЖП), особенно базальные сегменты [2]. Описаны редкие случаи вовлечения перикарда (с возможным плевральным выпотом) и эндокарда (в т. ч. и клапанного), но обычно при распространении из толщи миокарда [10].…”
unclassified